Short Communication: Digenea parasites in giant mudskipper (Periopthalmodon schlosseri) in Kuala Lupak Village, South Kalimantan, Indonesia - Hidayaturrahmah Hidayaturrahmah; HERI BUDI SANTOSO; DESY NURAPRIANA; BADRUZSAUFARI; MUHAMAT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hidayaturrahmah, Santoso HB, Nurapriana D, Badruzsaufari, Muhamat. 2019. Short Communication: Digenea parasites in giant mudskipper (Periopthalmodon schlosseri) in Kuala Lupak Village, South Kalimantan, Indonesia. Biodiversitas 20: 3782-3787. Parasites are organisms that impart detrimental effects on their host. Monogenea which are generally ectoparasites and digenea which are endoparasites are the most common parasites which invade fish. This research was aimed to find out the existence of monogenean and digenean parasites as well as their species in giant mudskipper or timpakul fish (Periopthalmodon schlosseri) in Kuala Lupak Village, South Kalimantan, Indonesia. Employing 25 giant mudskipper which was randomly collected from Kuala Lupak Village, South Kalimantan, this study explored the presence of ectoparasites and endoparasites on the mucous, fins, gills, intestines, stomach, and meat of the fish. The results showed that only digenean parasites were found in the giant mudskipper (Periopthalmodon schlosseri). The digenean parasites found to come from Opecoeloides genus and Buchepalidae family, metacercariae cysts, and parasites of the nematode phylum. Monogenea parasites were not found due to low fish-density, fish behavior that is rarely in the water, and adequate nutrition which is the opposite of growth-supporting factors of monogenean. Parasitic infection could occur because the fish eat some intermediate hosts of digenea, such as snails and other fish. Besides, the condition of waters that have been contaminated with digenean eggs allows the life cycle of the digenean to continue in fish.